Survei Pasar Kerja Dan Animo Masyarakat Untuk Kuliah di Jurusan Kesehatan Lingkungan - Tuntas Bagyono; Sri Muryani; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2008)
The study was aimed: to reveal peple’s knowledge about the existence of envi-ronmental health department (JKL), and Sanitarian as one of health professi-ons; to understand the magnitude of people’s interest to study at JKL and the corresponding influencing factors; and to understand the competencies of a Sanitarian needed by industries and governmental institutions as the users. The study conducted survey method and employed questionnaire as data collection instrument. The results showed that 45,45% of respondents had heard about Sanitarian and 22,02% had known the profession’s duties. The percentages were significantly different with those of Nurse. Meanwhile, people’s interest to study at JKL was 50,88% of that for Nursing Department. On the other hand, 73,2% of respondents from Industries and governmental insitutions agreed that Sanitarian as profession were relevant with ISO 14000 and OHS sertification programme, and 46,7% of them suggested that sanita-rian should have competencies which related with waste processing including the toxic and dangerous ones.